Using Music and Songs to Enhance L2 Vocabulary in Kindergarten School - Kusuma, Alvita Rahma Marta ((JELE) Journal Of English Language and Education, 2020)
The use of songs as a media for learning has long been favored by both teachers and students in kindergarten. However, whether using songs as a learning media will be effective for improving students’ vocabulary both in depth and breadth as well as improving their foreign language skills still needs further investigations. This study aims to determine and investigate whether songs can help children improve and develop vocabulary and their foreign languages. This research was taken by means of a test conducted on children in kindergarten. Several pre-test and test will be conducted to measure the child's ability to master L2. Songs can make student or children pay attention to the material. In this study, I will use two songs. After listening to the songs, the student will write the words that they listened and then check the words that they were familiar or not. The group participating in the study was 20 children in kindergarten aged 5-6 years, who have used songs as learning media. In this study, the students speak with their mother language and English is learned as a foreign language. The ability of children in L2 can be measured through tests that are tested on children. Some pre-test and test conducted are proven to be able to measure a child's ability to memorize vocabulary in L2. However, several obstacles may be found in this research. As expected with the research conducted, can make children learn and build interest in learning a foreign language and memorizing or even mastering a foreign language.